2019
DOI: 10.1111/btp.12660
|View full text |Cite
|
Sign up to set email alerts
|

Beta diversity of aquatic invertebrates increases along an altitudinal gradient in a Neotropical mountain

Abstract: Mountains harbor rich biodiversity and high levels of endemism, particularly due to changes in environmental conditions over short spatial distances, which affects species distribution and composition. Studies on mountain ecosystems are increasingly needed, as mountains are highly threatened despite providing ecosystem services, such as water supply for half of the human population. We aimed to understand the patterns and drivers of alpha and beta diversities of aquatic invertebrates in headwater streams along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 81 publications
3
30
1
1
Order By: Relevance
“…Similar to Castro et al (2019), we found that elevation range was a more important driver for Bray-Curtis beta diversity among stream F I G U R E 3 Proportion of taxa turnover and nestedness for Jaccard dissimilarity (left map) and Bray-Curtis distance (right map) for average pairwise beta diversity among sampling sites and seasons in each stream site sites than dissolved oxygen. Other authors have reached different conclusions for fish in Amazonian streams (Leal et al, 2018), macroinvertebrates in Cerrado streams (Castro et al, 2018;Firmiano et al, 2021), and fish in Cerrado streams (Pompeu et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar to Castro et al (2019), we found that elevation range was a more important driver for Bray-Curtis beta diversity among stream F I G U R E 3 Proportion of taxa turnover and nestedness for Jaccard dissimilarity (left map) and Bray-Curtis distance (right map) for average pairwise beta diversity among sampling sites and seasons in each stream site sites than dissolved oxygen. Other authors have reached different conclusions for fish in Amazonian streams (Leal et al, 2018), macroinvertebrates in Cerrado streams (Castro et al, 2018;Firmiano et al, 2021), and fish in Cerrado streams (Pompeu et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…The CR occupies < 1% of Brazil and yet hosts 15% of its plant species, including 40% endemics (Silveira et al., 2019). The synergy among environmental filters, geographical barriers related to changes in altitude and slope, and interactions between species is an important driving force for a wide variety of floral and faunal adaptations and speciation in the CR (Castro et al., 2019; Fernandes, 2016; Fernandes et al., 2018; Silveira et al., 2016). The CRs have been destroyed at alarming rates and these disturbances are reflected in their springs and headwater streams (Callisto et al., 2019; Callisto, Solar, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…siltation and water quality alteration; Kaufmann et al., 1999; Macedo et al., 2018). Thereby, the high importance of environmental filters is not surprising, as both natural and anthropogenic environmental factors are strong drivers of macroinvertebrate communities in the Neotropical savanna (Castro et al., 2019). The higher importance of environmental distance in SS and TM can be attributed to a higher variance of local physical habitat variables compared to the other two HUs (Callisto et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, and in accordance to previous studies, Sorensen's overall dissimilarity increased with increasing glacial influence (which is significantly correlated with altitude, Supp. Table S2) (Finn et al, 2013;Castro et al, 2019). This process could be explained by an increment of environmental heterogeneity between sites, which in turn, increases regional diversity Crespo-Pérez et al, 2020).…”
Section: 97mentioning
confidence: 99%